Applying Medical Ethics to the Informed Consent Process: Minimizing Legal Risks for Healthcare Professionals - Setyarini Setyarini; D. Bagus Perdana; Marsudi Dedi Putra (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, informed consent constitutes an ethical and legal process that safeguards patient autonomy while providing legal certainty for medical professionals. In practice, however, informed consent may still be reduced to an administrative formality, creating a gap between das sollen and das sein, particularly in communication, patient understanding, documentation, and compliance with professional standards. This study aims to analyze the application of medical ethics in the informed consent process, identify factors affecting its effectiveness, and examine its implications for the legal risks faced by medical professionals. This study employs normative legal research using statutory and conceptual approaches. Primary legal materials consist of health-related legislation, particularly Law Number 17 of 2023 on Health, while secondary materials comprise legal scholarship, medical ethics literature, and relevant scientific articles. The materials are analyzed using descriptive-analytical and prescriptive methods. The findings indicate that the effectiveness of informed consent depends on the quality of information, communication, decision-making capacity, documentation, and compliance with professional standards. Substantive application of medical ethics strengthens the legitimacy of medical interventions while serving as a preventive mechanism for minimizing disputes and potential legal liability of medical professionals.